The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/pola.23672
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly of well‐defined amphiphilic polymeric miktoarm stars, dendrons, and dendrimers in water: The effect of architecture

Abstract: Five polymeric architectures with a systematic increase in architectural complexity were synthesized by “click” reactions from a toolbox of functional linear polymers and small molecule linkers. The amphiphilic architectures ranged from a simple 3‐miktoarm star block copolymer to the more complex third generation dendrimer‐like block copolymer, consisting of polystyrene (PSTY) and polyacrylic acid (PAA). Micellization of these architectures in water at a pH of 7 under identical ionic strength gave spherical mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 47 publications
3
25
0
Order By: Relevance
“…However, TEM images of the micelles showed that the particles were smaller than that found by DLS, which is consistent with the literature 49. That may be because the diameter measured by TEM was representative of the dry PS core and collapsed PIL corona state of the micelles,50 and the size by DLS measurement was contributed by the corona stretching in solution.…”
Section: Resultssupporting
confidence: 88%
“…However, TEM images of the micelles showed that the particles were smaller than that found by DLS, which is consistent with the literature 49. That may be because the diameter measured by TEM was representative of the dry PS core and collapsed PIL corona state of the micelles,50 and the size by DLS measurement was contributed by the corona stretching in solution.…”
Section: Resultssupporting
confidence: 88%
“…water comes to the probe rather than the probe to the water). (2) Looping might indeed occur with 1 and 2, but it is abnormal, which is to say that conventional surfactants with methyl group termini do not act similarly. Although one could argue that if our innocuous acetylene probe was not trustworthy, then all that literature work with huge polar probes would be even more suspect, we preferred to accept probe ambiguity as an annoying fact of life.…”
Section: Examples Of Self-assembliesmentioning
confidence: 97%
“…The synthesis and examination of new self-assembling compounds have drawn international attention, as illustrated here via an incomplete and arbitrary listing: Argentina (amphiphilic cyclodextrins) [1]; Australia (amphiphilic dendrimers) [2]; Brazil (sugar-based surfactants) [3]; Canada (amphiphilic copolymers) [4]; China (chiral surfactants) [5]; France (noncovalent amphiphiles) [6]; Germany (bolaamphiphiles) [7]; India (multiple-headgroup surfactants) [8]; Italy (gemini surfactants) [9]; Iran (cleavable surfactants) [10]; Japan (p-electronic amphiphiles) [11]; Korea (T-shaped amphiphiles) [12]; The Netherlands (carbohydrate-based gemini surfactants) [13]; Portugal (amino acid-based amphiphiles) [14]; Spain (urea-based surfactants) [15]; Sweden (heterogemini surfactants) [16]; United Kingdom (light-sensitive surfactants) [17]; and United States (redox-active surfactants) [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along this line, the "click" chemistry between alkyne and azide groups was applied as a coupling reaction in the synthesis of dendrimer-like star polymers. As shown in Scheme 21, combination of copper wire catalyzed "click" chemistry, ATRP of styrene or acrylates, and the transformation of alkylbromide terminus into azido end group led to the formation of miktoarm dendrimer-like star polymers [65][66][67]. Three-arm star polymer bearing three azido termini derived from alkylbromides was coupled with AB-type diblock copolymers with alkyne groups at the junction to yield dendrimer-like miktoarm star terpolymers [68].…”
Section: Scheme 18mentioning
confidence: 99%